BOTTOM SEDIMENTS IN DELTAIC SHALLOW-WATER AREAS – ARE THEY SOILS? - Anna N. Tkachenko; Maria I. Gerasimova; Michael Yu. Lychagin; Nikolay S. Kasimov; Salomon B. Kroonenberg (Geography, Environment, Sustainability)
This article is based on long-term research of aquatic landscapes in the VolgaRiver delta which was held in 2010–2012 and included investigation and sampling of bottom sediments in deltaic lagoons, fresh-water bays, small channels, oxbow lakes, and part of the deltaic near-shore zone. Contrasting hydrological regime and suspended matter deposition together with huge amount of water plants in the river delta provide for the formation of different types of subaquatic soils. The purpose of this research is to reveal the properties of the subaquatic soils in the Volga River deltaic area and to propose pedogenetic approaches to the diagnostic of aquazems as soil types. It is suggested to name the horizons in aquazems in the same way as in terrestrial soils in the recent Russian soil classification system, and apply symbols starting with the combination of caps – AQ (for “aquatic”). The aquazems’ horizons are identified and their general properties are described. Most typical of aquazems is the aquagley (AQG) horizon; it is dove grey, homogeneous in color and permeated by clay. The upper part is usually enriched in organic matter and may be qualified for aquahumus (AQA) or  aquapeat (AQT) horizons. In case of active hydrodynamic regime and/or strong mixing phenomena, the oxidized (AQOX or aqox) horizon, or property could be formed. It is yellowish-grey, thin, and depleted of organic matter. The main types of aquzems specified by forming agents and combinations of horizons are described.